No theory: An explanation of the lack of consistency in cross-country health care comparisons using non-parametric estimators - Richard Gearhart (Health Economics Review, 2016)
Since 2000 several papers have examined the efficiency of healthcare delivery systems worldwide. These papers have extended the literature using drastically different input and output combinations from one another, with little theoretical or empirical support backing these specifications. Issues arise that many of these inputs and outputs are available for a subset of OECD countries each year. Using a common estimator and the different specifications proposed leads to the result that efficiency rankings across papers can diverge quite significantly, with several countries being highly efficient in one specification and highly inefficient in another. Broad input-output measures that are collected annually provide consistent efficiency rankings across specifications, compared to specifications that utilize specific measures collected infrequently. This paper also finds that broad output measures that are not quality-adjusted, such as life expectancy, seem to be a suitable alternative for infrequently collected quality-adjusted output measures, such as disability adjusted life years.
Keywords: C14; I11; I12; I18; 330; United States healthcare; Cross-country healthcare comparison; Production efficiency; Order-α; OECD